Conceptual Design of Deployment Structure of Morphing Nose Cone. (3rd April 2013) - Li, Junlan; Wu, Jianing; Yan, Shaoze
Abstract : For a reusable space vehicle or a missile, the shape of the nose cone has a significant effect on the drag of the vehicle. In this paper, the concept of morphing nose cone is proposed to reduce the drag when the reentry vehicle flies back into the atmosphere. The conceptual design of the structure of morphing nose cone is conducted. Mechanical design and optimization approach are developed by employing genetic algorithm to find the optimal geometric parameters of the morphing structure. An example is analyzed by using the proposed method. The results show that optimal solution supplies the minimum position error. The concept of morphing nose cone will provide a novel way for the drag reduction of reentry vehicle. The proposed method could be practically used for the design and optimization of the deployable structure of morphing nose cone.